SRATEGI GURU DALAM MENGAJAR ANAK AUTIS DENGAN HAMBATAN WICARA DI SLB QALBU INSANI PADANG SIDIMPUAN - Nur Hakimah; Hayatun Nadiroh; Aulia Sari Marbun; Rizki Fitrah Al-Fadila Lubis; Febriyantika Pasaribu (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2026)
This study aims to describe the strategies used by teachers in teaching children with autism and speech impairments at SLB Qolbu Insani Padangsidimpuan. A qualitative method was employed, with data collected through observation, in-depth interviews, and documentation. The results indicate that teachers apply contextual and individualized strategies, such as life skills training, providing motivation, and using visual and concrete media tailored to each child's characteristics. A key strategy identified is the utilization of the Behavior Analysis Application to analyze children's behavior, design individualized interventions, deliver positive reinforcement, and involve parents in the learning process. A case study of a student named Zaren highlights the importance of a patient and gradual approach, as well as family support, in fostering the child's development. Despite limited resources. teachers actively serve as facilitators and motivators. These findings contribute theoretically understanding teaching strategies for children with special needs and can practically serve as a reference for teacher training development and inclusive education policies in special schools.